2015
DOI: 10.1007/s11119-015-9412-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving in-season estimation of rice yield potential and responsiveness to topdressing nitrogen application with Crop Circle active crop canopy sensor

Abstract: In-season site-specific nitrogen (N) management is a promising strategy to improve crop N use efficiency and reduce risks of environmental contamination. To successfully implement such precision management strategies, it is important to accurately estimate yield potential without additional topdressing N application (YP 0 ) as well as precisely assess the responsiveness to additional N application (RI) during the growing season. Previous research has mainly used normalized difference vegetation index (NDVI) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 57 publications
5
53
2
3
Order By: Relevance
“…3b). This is similar to Cao et al (2016), who found a comparable correlation ( r 2 = 0.63) in their experiments at a single location. Others (e.g., Harrell et al, 2011; Yao et al, 2012) have reported a poorer relationship between NDVI and grain yield with r 2 values ranging from 0.36 to 0.44.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3b). This is similar to Cao et al (2016), who found a comparable correlation ( r 2 = 0.63) in their experiments at a single location. Others (e.g., Harrell et al, 2011; Yao et al, 2012) have reported a poorer relationship between NDVI and grain yield with r 2 values ranging from 0.36 to 0.44.…”
Section: Discussionsupporting
confidence: 91%
“…Comparatively, there have been relatively few such studies in rice. Some have tested the ability of NDVI to assess rice N status (Zhu et al, 2007; Gnyp et al, 2014; Yao et al, 2014; Lu et al, 2017) and few have used NDVI to develop in‐season yield predictions (Harrell et al, 2011; Yao et al, 2012; Cao et al, 2016). However, most of these studies have focused their research on single sites, leaving at question the scalability of their findings to other sites representing different soils and management practices.…”
mentioning
confidence: 99%
“…However, the NDVI may saturate under moderate-to-high biomass conditions at later growth stages [28][29][30]. The RE-based VIs have been proven to be sensitive to crop canopy chlorophyll and N variation, even under the high biomass condition [7,[31][32][33][34]. Since both RapidEye and WorldView-2 have the RE band, the question of how RE-based indices could improve the estimation of rice N status needed to be answered.…”
mentioning
confidence: 99%
“…The CV 710 and CV 735 values were higher than CV 660 . Several studies showed the advantage of using red‐edge–based VIs for monitoring plant crop growth (Cho and Skidmore, 2006; Peng and Gitelson, 2012; Cao et al, 2015). Red‐edge band sits between the red to near infrared bands (680–740 nm) where light energy is strongly absorbed by chlorophyll pigments and at the same time highly reflected by leaf structure.…”
Section: Resultsmentioning
confidence: 99%
“…Reports in the literature indicated the use of red‐edge–based VIs improved the monitoring of plant conditions, especially as plants approached maturity and complete canopy closure (Mutanga and Skidmore, 2004; Cao et al, 2015). In the current study red‐edge VIs and their CVs had strong negative relationships at the early tillering stage (Fig.…”
Section: Resultsmentioning
confidence: 99%